PANTUN MELAYU PONTIANAK SEBAGAI SARANA PEMBENTUK KARAKTER BANGSA - Gunta Wirawan (Balai Bahasa Kalimantan Barat, 2020)
Pontianak Malay Pantun uses Pontianak dialect Malay as the media forming the national character. This rhyme is usually spoken in events such as engagement, marriage, religion, or other traditional events. For the Malay people, pantun does not only function as a subtle delivery of values and advice, but also as a means of communication and a medium for storing customs. The purpose of this study is to describe the Pontianak Malay pantun which has the value of forming the nation's character. The method used is descriptive qualitative form with a documentary study approach. The data source in this study is Pontianak Malay pantun collected by Abd. Rachman Abror. This book was published by LKiS Yogyakarta in 2009. The results showed that Pontianak Malay pantun has national character values, namely human behavior in relation to God, human behavior in relation to oneself, human behavior in relation to fellow human beings, human behavior in relation to environment, human behavior in relation to nationality.